The effects of CIGS absorber layer thickness and band gap energy on the performance of CIGS thin film solar cell: a numerical simulation - Junaidu, Mustapha Hassan; Ying, Josephine Chyi Liew; Mohammed Aliyu, Mannir; Bello, Musa; Kabeer, Sulayman Muhammad; Shuaibu, Alhassan; Talib, Zainal Abidin (International Scientific Organization, 2023)
This work examines the effects of the Copper Indium Gallium Selenide (CIGS) absorber layer on the performance of a CIGS photovoltaic cell through numerical simulation using Analysis of Microelectronic and Photonic Structure – 1Dimensional (AMPS – 1D) software. The band gap energy and thickness of the CIGS absorber layer were varied while keeping the other properties, such as carrier concentration of the CdS buffer and ZnO window layers, constant. The optimum value obtained for the band gap energy of the CIGS absorber layer was 1.2 eV, while the thickness was 2500 nm. These optimum values were used to simulate the optimum CIGS solar cell with 83.2% fill factor, 0.718 V open circuit voltage, 28.8 mA/cm2 short circuit current density, and conversion efficiency of 17.197%.